2020
DOI: 10.1016/j.ijrobp.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Image Guided Ablative Prostate Cancer Radiation Therapy: Results From the TROG 15.01 SPARK Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…The analysis of the MER plans which incorporated the effect of prostate residual intrafraction motion during dose delivery with beam gating and repositioning when necessary, showed that PTV coverage was slightly reduced and hotspots increased in accordance with prior reports [26][27][28]. However, the median CTV D 98% was 18.1 Gy (i.e., 95% of the prescribed dose) though in one patient (#6) dropped to 17.8 Gy (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The analysis of the MER plans which incorporated the effect of prostate residual intrafraction motion during dose delivery with beam gating and repositioning when necessary, showed that PTV coverage was slightly reduced and hotspots increased in accordance with prior reports [26][27][28]. However, the median CTV D 98% was 18.1 Gy (i.e., 95% of the prescribed dose) though in one patient (#6) dropped to 17.8 Gy (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…PTV margins in combination with motion mitigation strategies allowed maintaining an adequate target coverage using a 3-mm gating threshold. These findings compare favorably with results of the TROG 15.01 SPARK trial, showing that with real-time kilovoltage-based IGRT intrafraction monitoring, no treatment had a prostate CTV D 98% dose 5% less than planned [28].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2 There has been huge progress in cancer treatment, including surgery, radiotherapy, chemotherapy, and immunotherapy. [3][4][5] Chemotherapy remains the most common therapeutic modality due to its high efficiency. However, clinical trials have proven that chemotherapy has many problems, such as poor targeting, systemic effects, and indiscriminate destruction of normal cells, resulting in various side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Once the treatment beam was manually gated, the couch was shifted to reposition the patient such that the prostate was returned to its initial planned position. Gating was available for 171 fractions, but treatment was not completed using KIM for 5 fractions due to various technical issues [24]. A total of 166 gating fractions were included in this analysis, and 65 of these fractions observed prostate motion that exceeded the motion threshold, requiring intervention.…”
Section: Motion Adaptation Processmentioning
confidence: 99%